PERSEPSI PETANI TERHADAP PERTANIAN ORGANIK DI KABUPATEN BANYUMAS - Emy Triyanti; Irene Kartika Eka Wijayanti; Akhmad Rizqul Karim (Jurnal Pertanian Agros, 2025)
Declining agricultural productivity and crop failures caused by changing rainfall patterns, rising temperatures, and reduced water availability are negative impacts of climate change on agriculture. Threats to the agricultural sector are not only influenced by the impacts of climate change, but also the implementation of conventional farming systems. Implementing an environmentally friendly farming system that is adaptive to climate change and able to improve farmer welfare is one solution to mitigate the negative effects of conventional farming, namely organic farming. Farmer perception is how farmers see, think, and respond to something. Farmer perception influences their decision to implement organic farming. The study aimed to analyze farmers' perceptions of organic farming in terms of economic sustainability, ecological sustainability, and social sustainability and to identify the influence of factors on farmers' perceptions. The study was conducted in Dawuhan Village, Banyumas District, and Lemberang Village, Sokaraja District, using quantitative descriptive approaches with a census method. Farmers' perceptions of organic farming in terms of economic sustainability were categorized as very high (80.6%), very high in terms of ecological sustainability (71%), and very high in terms of social sustainability (83.9%). Factors that significantly influenced farmers' perceptions of organic farming were ease of organic cultivation and relative profitability. Ease of obtaining production inputs, the role of groups and stakeholders did not significantly influence farmers' perceptions.